Penerapan Sanksi Kepada Perusahaan Yang Tidak Melaksanakan Corporate Social Responsibility (CSR) Terhadap Pekerja - Luh Made Ramadia Sari; Ida Bagus Erwin Ranawijaya (International Forum of Researchers and Lecturers, 2023)
Basically Corporate Social Responsibility (CSR) is manifested in the social role of a company or Limited Liability Company (PT) towards the company's internal environment, namely the welfare of its workers' lives. The existence of a level of welfare for workers is one way or strategy that can increase the participation of workers, motivation and loyalty of the workers. This problem is included in the Law of the Republic of Indonesia Number 40 of 2007 concerning Limited Liability Companies and in addition to the Law Number 25 of 2007 concerning Investment (UUPM) Article 34, namely